Exogenous glutathione attenuates lead-induced oxidative stress in wheat by improving antioxidant defense and physiological mechanisms. Issue 1 (1st January 2018) - Hasanuzzaman, Mirza; Nahar, Kamrun; Rahman, Anisur; Mahmud, Jubayer Al; Alharby, Hesham F.; Fujita, Masayuki
ABSTRACT: This study aims at investigate how exogenous glutathione (GSH, 1.0 mM) affects the oxidative stress and antioxidant defense in wheat seedlings under lead (Pb) stress [0.5 and 1.0 mM Pb(NO3 )2 ]. Lead treatment decreased growth, leaf relative water content, and chlorophyll (chl) content whereas raised proline (Pro) level. Lead stress increased H2 O2 content, generation rate, and membrane lipid peroxidation. Addition of Pb also disrupted antioxidant enzyme activities and status of endogenous ascorbate and GSH pool. The increase of methylglyoxal was evident under Pb stress. Glutathione supplementation under Pb stress increased antioxidant redox pool and augmented the activities of antioxidant enzymes, and decreased ROS production. Exogenous supplementation of GSH reverted the increase in the methylglyoxal level due to Pb stress due to increased activities of glyoxalase enzymes. Exogenous GSH also regulated Pro, well-maintained tissue water status and prevented chl degradation and increased plant growth and biomass.Abbreviations: AO- ascorbate oxidase; APX- ascorbate peroxidase; AsA- ascorbic acid (ascorbate); BSA- bovine serum albumin; CAT- catalase; CDNB-1-chloro-2, 4-dinitrobenzene; chl- chlorophyll; DHA- dehydroascorbate; DHAR- dehydroascorbate reductase; DTNB- 5, 5′-dithio-bis (2-nitrobenzoic acid); EDTA- ethylenediaminetetraacetic acid; Gly I- glyoxalase I; Gly II- glyoxalase II; GR- glutathione reductase; GSH- reduced glutathione; GSSG- oxidized glutathione; GPX- glutathione peroxidase; GST- glutathione S -transferase; MDA- malondialdehyde; MDHA- monodehydroascorbate; MDHAR- monodehydroascorbate reductase; MG- methylglyoxal; NADPH- nicotinamide adenine dinucleotide phosphate; NBT- nitroblue tetrazolium chloride; Pb- lead; PEG- polyethylene glycol; Pro- proline, ROS- reactive oxygen species; RWC- relative water content; SLG- S -d -lactoylglutathione; SOD- superoxide dismutase; TBA- thiobarbituric acid; TCA- trichloroacetic acid.